An Equivalent Rotor Speed Compensation Control of PMSG-Based Wind Turbines for Frequency Support in Islanded Microgrids - Zhong, Cheng; Lv, Yueming; Zhou, Yang; Li, Huayi (Frontiers in Energy Research, 2021)
Frequency regulation is a critical issue in the islanded microgrids, especially the integration of high penetration of the wind power generator. In order to provide inertial and primary frequency support to the wind power system, this article proposes an equivalent rotor speed compensation control scheme of PMSG for frequency support in the islanded microgrids. A new variable combining pitch angle and rotor speed is defined as the equivalent rotor speed. The equivalent rotor speed versus de-loaded power curve is designed to preserve a part of active power among the whole wind speed area. And the inertia control scheme is optimized by adding a virtual compensation variable to the equivalent rotor speed to obtain the reference of the machine-side converter control loop. Adopting the proposed scheme, the PMSG-based wind turbine can achieve a similar frequency regulation performance to synchronous generators. Simulation results demonstrate the feasibility and effectiveness of the proposed control scheme.